Stress response in honeybees is associated with changes in task-related physiology and energetic metabolism. (April 2017) - Bordier, Célia; Suchail, Séverine; Pioz, Maryline; Devaud, Jean Marc; Collet, Claude; Charreton, Mercedes; Le Conte, Yves; Alaux, Cédric
Graphical abstract: Highlights: Stress response did not change according to task specialisation. Immune and heat stress affected the expression of task related genes ( vg and jhe ). Sublethal exposure to pesticides did not modify the expression of vg and jhe genes. Energetic metabolism tended to decrease upon stress exposure. Abstract: In a rapidly changing environment, honeybee colonies are increasingly exposed to diverse sources of stress (e.g., new parasites, pesticides, climate warming), which represent a challenge to individual and social homeostasis. However, bee physiological responses to stress remain poorly understood. We therefore exposed bees specialised in different tasks (nurses, guards and foragers) to ancient (immune and heat stress) or historically more recent sources of stress (pesticides), and we determined changes in the expression of genes linked to behavioural maturation (vitellogenin – vg and juvenile hormone esterase – jhe ) as well as in energetic metabolism (glycogen level, expression level of the receptor to the adipokinetic hormone – akhr, and endothermic performance). While acute exposure to sublethal doses of two pesticides did not affect vg and jhe expression, immune and heat challenges caused a decrease and increase in both genes, respectively, suggesting that bees had responded to ecologically relevant stressors. Since vg and jhe are expressed to a higher level in nurses than in foragers, it is reasonable to assume that an immune challenge stimulated behavioural maturation to decrease potential contamination risk and that a heat challenge promoted a nurse profile for brood thermoregulation. All behavioural castes responded in the same way. Though endothermic performances did not change upon stress exposure, the akhr level dropped in immune and heat-challenged individuals. Similarly, the abdomen glycogen level tended to decline in immune-challenged bees. Altogether, these results suggest that bee responses are stress specific and adaptive but that they tend to entail a reduction of energetic metabolism that needs to be studied on a longer timescale.